SOSIALISASI DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN PSIKOLOGIS ANAK USIA DINI: Socialization of the Impact of Using Gadgets on Early Chilhood Psychological Development - Simanjuntak, Putri Aprianti Boru; Tung, Cintia; Amseke, Fredericksen Victoranto (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
In the digital era, children grow up with easy access to gadgets, such as smartphones, tablets and laptops. Gadgets can provide unlimited access to information, entertainment, and communication. But on the one hand, gadgets have a negative impact on their users.  The aim of this community service activity is to provide knowledge to parents and teachers about the impact of using gadgets on children's psychological development from an early age. The method for community service is a qualitative method, interactive lectures, learning discussions about the influence of gadgets on early childhood development involving 23 parents and 2 teachers at PAUD Taruna Elim Kuanino. The results of this community service activity found that parents and teachers were able to understand that gadgets not only have a positive impact but there are also negative impacts from excessive use of gadgets, which can affect the psychological development of early childhood. Community Service Activities (PKM) can increase the knowledge and skills of PAUD teachers, especially parents, in encouraging children to use gadgets more wisely.